An Analysis of Reasons Behind Difficulties in Understanding Life Science Concepts of Undergraduate Students in Universities of Chhattisgarh - Kumar, Sujeet; Dhapola, Janki (Advances in Social Sciences Research Journal, 2023)
The purpose of the study was to find out the differences between the reasons behind difficulties of life science concepts of under graduate zoology students of Guru Ghasidas Vishwavidyalaya and Atal Bihari Vajpayee University Bilaspur, (C.G.) Chhattisgarh state. For the present study two hundred (200) B.Sc. 3rd year Zoology students of Guru Ghasidas Vishwavidyalaya and Atal Bihari Vajpayee University Bilaspur, (C.G.), India was selected. For the present study researcher has selected students those who are studying in B.Sc. 3rd year at the time of data collection. For the collection of data researcher has constructed “Reasons Behind Difficulties Inventory” (RBDI)” with reliability 0.75measured through test, re-test method and to find out the difference chi square test was used and implemented purposive sampling technique. In this present study only twenty (20) life science concepts of B.Sc. 3rd year Zoology subject were taken and remaining zoology concepts of B.Sc. 3rd year has not been considered. After collection of data through this tool researcher has analysed the quantitative data by using descriptive statistics. The study concluded that there was a significant difference between graduate zoology students of Guru Ghasidas Vishwavidyalaya and Atal Bihari Vajpayee University Bilaspur, (C.G.) in all the selected ten reasons at 0.025level of significance.